STRATEGI PRAGMATIK BAHASA HUMOR DALAM ACARA “MARIO TEGUH GOLDEN WAYS” DI METRO TV - Enie Hendrajati (Jurnal Sosial Humaniora, 2017)
Speech humor in MTGW program is assumed as a "good practice" ofpragmatic strategy to entertain, inspire and motivate audience. The focusand objective of this study is to get a description of the pragmatic strategy ofharmonizing word choice, sentence, and humorous language in MTGWprogram. This research uses desciptive qualitative approach. Data in theform of humorous languages is collected by listening and recording. Themethod of analysis is padan and agih. The pragmatic strategy MT uses inthe MTGW program on Metro TV is to harmonize between lingual units ofwords, sentences, and language styles with humor and courtesy. MT uses alocusive and illocusive strategy with humorous tones and politeness inchoosing, organizing and producing every word, sentence, and style ofhumor. Through the choice of words, sentences, and language style, the MTuses pragmatic strategies in conveying his message as a motivator and theperlocutionary effect is that the audience becomes interested or entertained